Erk5 is a mediator to TGFβ1-induced loss of phenotype and function in human podocytes - Badshah, Irbaz I.; Baines, Deborah L.; Dockrell, Mark E. (Frontiers in Pharmacology, 2014)
Diabetic nephropathy is one of the most common causes of renal impairment. Podocytes are specialised cells integral to normal kidney physiology, however in diabetes injury occurs leading to compromised function which is a critical factor in the development of the disease. TGFβ1 is known to play a major role in glomerular damage. The atypical MAP kinase Erk5 is involved in pathways modulating cell survival, proliferation and phenotype. We have investigated the role of Erk5 in mediating TGFβ1-induced podocyte damage. Expression of Erk5 and activation by TGFβ1 (2.5 ng/ml) was investigated in transformed human podocytes in vitro. The effects of TGFβ and the role of Erk5, as determined by the use of an inhibitor of Erk5 phosphorylation BIX02188 (10 µM), was assessed in podocyte proliferation, motility, barrier function, phenotype and apoptosis. TGFβ1-induced proliferation and apoptosis of podocytes, whilst decreasing motility; proliferation was reduced by inhibiting Erk5 phosphorylation, whereas apoptosis was not nor was motility restored. TGFβ1 induced an alteration of cellular phenotype, as determined by a reduction in the expression of P-cadherin and increased α-SMA, in addition to reducing barrier function. Both phenotypic change and loss of barrier function were markedly reduced by pre-treatment with BIX02188. These results describe for the first time the expression of Erk5 in podocytes and identify it as a potential target for the treatment of diabetic renal disease.